Effects of Dietary Vitamin C on the Growth Performance, Biochemical Parameters, and Antioxidant Activity of Coho Salmon Oncorhynchus kisutch (Walbaum, 1792) Postsmolts - Cong-mei Xu; Hai-rui Yu; Ling-yao Li; Min Li; Xiang-yi Qiu; Xiao-qian Fan; Yan-lin Fan; Ling-ling Shan (Aquaculture Nutrition)
Vitamin C (VC) plays an essential role in fish physiological function and normal growth. However, its effects and requirement of coho salmon Oncorhynchus kisutch (Walbaum, 1792) are still unknown. Based on the influences on growth, serum biochemical parameters, and antioxidative ability, an assessment of dietary VC requirement for coho salmon postsmolts (183.19±1.91 g) was conducted with a ten-week feeding trial. Seven isonitrogenous (45.66% protein) and isolipidic (10.76% lipid) diets were formulated to include graded VC concentrations of 1.8, 10.9, 50.8, 100.5, 197.3, 293.8, and 586.7 mg/kg, respectively. Results showed that VC markedly improved the growth performance indexes and liver VC concentration, enhanced the hepatic and serum antioxidant activities, and increased the contents of serum alkaline phosphatase (AKP) activity, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and total cholesterol (TC) whereas decreased the serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) activities, and triglyceride (TG) level. Polynomial analysis showed that the optimal VC levels in the diet of coho salmon postsmolts were 188.10, 190.68, 224.68, 132.83, 156.57, 170.12, 171.00, 185.50, 142.77, and 93.08 mg/kg on the basis of specific growth rate (SGR), feed conversion ratio (FCR), liver VC concentration, catalase (CAT), hepatic superoxide dismutase (SOD) activities, malondialdehyde (MDA) content, and serum total antioxidative capacity (T-AOC), AKP, AST, and ALT activities, respectively. The dietary VC requirement was in the range of 93.08–224.68 mg/kg for optimum growth performance, serum enzyme activities, and antioxidant capacity of coho salmon postsmolts.